Pelayanan Pendaftaran Pasien Rawat Jalan di Rumah Sakit Elisabeth Medan - Theresia Elen Novia Ziraluo; Agnes Louise Lasmaida; Febri Sembiring (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Abstract Hospital outpatient registration services are a phenomenon that refers to the actions or activities of a system within a hospital or health service facility which aims to maintain and improve health, prevent and cure disease and restore health. Outpatient care is a medical service provided to patients not in the form of inpatient care. This study aims to see an overview of outpatient registration services at Santa Elisabeth Hospital, Medan. This research uses a descriptive design with a quantitative approach. The sample in this study consisted of 30 patients. In this research, researchers collected data using a questionnaire. This research was conducted in June 2024. The data was analyzed univariably. The research results showed that there were 15 patients who received good and good service (50%), 10 patients received adequate service (33.33%) and 5 patients received poor service (16.66%). In this case, Santa Elisabeth Hospital Medan must continue to maintain good and friendly services and improve poor services.